Waqf Financial reporting and transparency: Case of Ar-Raudhatul Hasanah Islamic Boarding School - Khaidar Rahmaini Jamila; Syed Musa Alhabshi (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2019)
This paper provides an insight on which standard that had to be applied for Islamic Boarding School’s financial statement and the gaps encountered while new accounting waqf is implemented. The existence of various financial statements format among waqf foundations these days is becomes a reason of this research. To be precise, Ar-Raudhatul Hasanah Islamic Boarding School is undertaken as an object analysis. This article will also introduce the new waqf accounting standard prepared by Institute of Indonesia Chartered Accountant and Central Bank of Indonesia. The methodology used in this research is qualitative research with purposive sampling as its sampling technique. Furthermore, finding of this research asserted that Ar-Raudhatul Hasanah Islamic Boarding School had been adopting the Statement of Government Accounting Standard (PSAP) number 01 concerning the presentation of financial statements and the Government Regulation Republic of Indonesia number 8 of 2006 in drafting their financial statements. However, the appropriate accounting standard for it is PSAK No. 45. Therefore, it has not fully implemented the components of financial statement in accordance with PSAK 45 due to the absence of statement of activity. This paper also revealed the encouragement to adopt new waqf accounting standard in preparing the financial statement and to publish it on the official website. Hence the benefit is to attract the interest of stakeholders in giving endowments as well as to eliminate the diversity format in recording financial transaction of waqf asset